Professor Builds Desktop High-Performance Computer. - Garber, Lee (Computer (00189162), 2007)
The article discusses a high-performance desktop computer built by professor Joel Adams of Calvin College and Tim Brom, a former student. The machine, dubbed Beowulf, can run at 26.25 gigaflops and cost $47.80 per gigaflop to construct. By comparison, a machine at Stanford University cost $109 per gigaflop. Beowulf incorporates multicore chips that communicate with each other using Gigabit Ethernet. Among applications the machine is powerful enough to run are those for molecular modeling and fluid dynamics.